Cascade Control Using Soft Sensor for Aldehide Column Energy Saving - Totok R. Biyanto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
The focus of this paper is to develop the control strategy on aldehyde distillation column. The objectives are to maintain the consistency of product’s composition, energy saving and optimum cost. The method is replacing the control structure from inferential control to cascade control using LV structure, with soft sensor to improve performance, reduce cost and increase reliability. The disturbance was given by a change in the mole flow rate of feed. Cascade control with LV structure was proposed to minimize Internal Absolute Error (IAE) and increase energy efficiency. The result of this research showed that cascade control with LV structure had a lower Integral Absolute Error (IAE) than inferential control structure, improved product composition consistency, and increased energy efficiency.